P-34 If death cafes are the answer, what is the question?. Issue Volume 6: Issue (2016)Supplement 1 (1st November 2016) - Green, Laura; Daley, Andrew; Ward, Andrea; Wilcock, Tracey
Abstract : Background: Death Cafes are seen as an increasingly important element of current approaches to improve public awareness of death. We address the question of diversity in Death Cafes and question the presumed inclusivity of current approaches. Methods: Four Death Cafes in three geographical areas were selected as the focus for the study. The Death Cafes took place in a town hall, a university students' union, a hospice and a pizzeria. Observational, website, social media and text analysis were used. Data collected included the method and language used to publicise the event; venue; demographics of attendees; reason for attendance; and a summary of the issues and topics discussed. Key findings: In spite of using a diversity of venues, the majority of attendees at all the Death Cafes were female professionals with a health/social care background. A wide range of issues were discussed: bereavement support needs were common themes in all events. Attendees valued the opportunity to network and engage with local services. Future directions: The Death Cafes attracted a relatively unrepresentative proportion of the local community. If they are to become more open and accessible it is necessary that consideration be given to aspects such as location, timing, publicity, style, facilitation and "ownership". Unobtrusive observation offered an effective means of evaluating subtle nuances in such events as well as capturing unmet support needs. The presentation will consider the future possibilities and limitations surrounding the Death Cafe concept.